Laman Web sebagai HWO (Home Work Online) dalam E-Learning - Eko Purnomo Purnomo (Universitas Muhammadiyah Ponorogo, 2020)
This research aims to develop and create an innovation in the world of education, namely the use of WEB pages that are used as online PR media. This research method uses research and development methods. The results in this study are found that the WEB page is very innovative when used as a medium in online homework, because teachers can monitor students who are learning or not. The novelty in this study is that the use of WEB pages as a homework media or homework has not been used in Indonesia. In this WEB page students cannot see the answers of other students, because this WEB system is confidential. One student has their own identification number to access this WEB, so it allows students to not be able to see their friends' answers. In addition, parents can monitor student learning activities while at school and their grades directly through the WEB. And can be done clinics between teachers and parents of students when students at school make mistakes.